Analisis Fairness terhadap Sistem Pembayaran Jasa Pengairan Sawah pada Petani Desa Bibrik Kecamatan Jiwan Kabupaten Madiun - Kusnul Ciptanila Yuni K; Iza Hanifuddin (Institut Agama Islam Negeri Ponorogo, 2022)
The purpose of this study is to find out how fair the application of irrigation of rice fields is in determining the consideration for irrigation services of rice fields according to John Rawls' idea of ​​justice. The research methodology in this study is qualitatively descriptive by processing primary and secondary data obtained through observation, interviews, and documentation in Bibrik village, Jiwan province, Madiun province. The result of the study is that the perception of fairness in the application of rice field irrigation is carried out from the irrigation stage, determination of fees for irrigation services of rice fields, and the water distribution mechanism is not always accurate, although it is. Designed so that there is no fairness, the fairness of the service will reflect the fairness of the water workers group. Standardization of payment for services is not the same in villages, whether it is the location of rice fields next to irrigation canals or vice versa so the fairness of services is expected to have a significant impact on farmers' education and bring about social upheavals. . The means of payment for this service is of two types: quality money and grain, so it is not fair between farmers and workers that grain is sold for more money than direct cash payments, which causes unrest in the company.